Outward foreign direct investment by emerging markets: evidence from Colombia - Castro Vega, Paula Ximena (2020)
Companies from emerging markets are increasingly engaging in internationalization processes through different modes of operation. The theoretical frameworks that seek to explain these processes are especially focused on companies in developed markets, and the information available on how these processes have arisen in less industrialized economies is scarce. In this order of ideas, there is ample space for research to understand internationalization processes in economies such as Colombia, which, despite not being at the level of other emerging economies such as China, India and even Brazil, is part of the group of countries that are projected to be economically stronger in the future. Given that the manufacturing sector is becoming one of the sectors with the most growth opportunities in Colombia, particularly the pharmaceutical industry, it was sought to work closely with a Colombian multinational with experience in operating internationally within the industry. Thanks to the collaboration of the main decision makers and strategic managers of the company, first-hand information was obtained to be examined, analyzed and evaluated in light of the existing theoretical frameworks related to processes of internationalization. Initially, the institution-based view and resource-based view frameworks were taken into account as they contribute to the explanation of the internationalization drivers of companies from emerging economies. Subsequently, the company's internationalization process was viewed from an economic and behavioral perspective through the lens of the Dunning's Eclectic Paradigm, the Uppsala model and the model of decision-makers' factors influencing the strategic decision-making process. The study therefore contributes to filling the gap in research regarding international strategy in emerging market enterprises.